Hubungan Word Of Mouth Marketing Dengan Loyalitas Pelanggan Produk Kesehatan Merek Xxx Di Serang Banten - Dede Oktini (Universitas Islam Bandung, 2011)
The Consumers gather information from several media campaigns including advertising and sales agents. They later told it to their relatives, or even their family, or they neighbor. This phenomenon is known as the Word Of Mouth (WOM). Word of mouth phenomenon is belived can boost purchases by the consumer, can give influence to certaint community, give more efficiency because WOM doesn’t need high budget (low budget), Wom able to create the positive image into one product, and also able to touch the affective side of consument, wheter using good advertising, the right-place promotion, or attractive online game, publication on newspaper, or held some event that will give good feedback that will be talked constantly by people. This research objective is to find the relation between word of mouth marketing with consumer loyality. The research method that being used is verificative method. Variable that will be tested are word of mouth marketing variable (x) and consumer loyality variable (y). the data collection technique on this research was done thourgh field research, which is direct interview, and spreading the questionnaire that using simple random sampling method. The data procces in this research using statistical calculation, with the use of rank spearman (rs)riietfud Variety of he tested is verificative riietfud (rs) correlation formala.The result of statistical calculation clearly shown that the word of mouth marketing marketing variables have an average or good enough correlation rate the amout of +0.586 with the customer loyality on XXX variable. That is means the better performance of the word of mouth merketing that’s been done, give impact to the increasing of the customer loyality rate. With the use of SPSS software, obtained probability number in the amount of 0.000 below 0, 05 point, thus it's mean how rejected and hi accepted, this result is supporting the hypothesis : there is a relationship bemeen the word of mourh marketing wth the customer loyality on XXX serang stockis.